2008
DOI: 10.15288/jsad.2008.69.834
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Alcoholism in Trinidad and Tobago

Abstract: The clinical course of alcoholism has been described as a series of distinct, alcohol-related life events that occur in an orderly sequence. However, whether that sequence differs, depending on ethnicity and country of origin, is less clear. The purposes of this study were to investigate the sequence and progression of alcohol-related life events in individuals of East Indian (Indo) and African (Afro) heritage on the islands of Trinidad and Tobago, and compare those results with data reported previously by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Ehlers et al 7 and Malcolm et al 8 investigated the clinical course of alcoholism using Schuckit’s instrument in a population of Native Americans/Alaska Natives and found a substantially similar clinical course to that of the participants described by Schuckit et al 3 , who were in the Collaborative Study for the Genetics of Alcoholism. Scott et al 9 evaluated the clinical course of alcoholism in a population of African Americans using the same criteria, and also verified that the clinical course was similar to that reported by Schuckit et al 3 , as did Montane-Jaime et al 10 who evaluated Trinidadians of African and East Indian descent. However, although each of these populations showed substantially the same order and progression of alcohol related life events, there were ethnic differences in the ages of onset, endorsement rates of individual alcohol-related life events, and the length of time from the occurrence of the first life event to the development of severe problems.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ehlers et al 7 and Malcolm et al 8 investigated the clinical course of alcoholism using Schuckit’s instrument in a population of Native Americans/Alaska Natives and found a substantially similar clinical course to that of the participants described by Schuckit et al 3 , who were in the Collaborative Study for the Genetics of Alcoholism. Scott et al 9 evaluated the clinical course of alcoholism in a population of African Americans using the same criteria, and also verified that the clinical course was similar to that reported by Schuckit et al 3 , as did Montane-Jaime et al 10 who evaluated Trinidadians of African and East Indian descent. However, although each of these populations showed substantially the same order and progression of alcohol related life events, there were ethnic differences in the ages of onset, endorsement rates of individual alcohol-related life events, and the length of time from the occurrence of the first life event to the development of severe problems.…”
Section: Introductionsupporting
confidence: 54%
“…810,22 In two studies, one in a Native American community sample 2 and one in Alaska Natives seeking treatment 8 , the alcohol related symptoms assessed, although occurring in the same order, appeared to develop at an earlier age and the time from the appearance of the first symptom and seeking help for those problems was shorter than what had been reported in the COGA study of primarily EuroAmericans. In another study, in the Navaho, the progression of 46 alcohol related life events, as described by Jellinek 1 , were evaluated in a group of 99 inpatients in an alcohol-detoxification center 6 .…”
Section: Discussionmentioning
confidence: 88%
“…In the same study, Indo-T also reported experiencing more blackouts, shakes, withdrawal, and health problems than Afro-T (Montane- Jaime et al, 2008).…”
Section: Response To Alcohol In Indo-t and Afro-tmentioning
confidence: 82%
“…drinking (Montane-Jaime et al, 2008), and report drinking more often and more drinks per occasion than Afro-T alcoholics (Montane-Jaime et al, 2006). In the same study, Indo-T also reported experiencing more blackouts, shakes, withdrawal, and health problems than Afro-T (Montane- Jaime et al, 2008).…”
Section: Response To Alcohol In Indo-t and Afro-tmentioning
confidence: 82%
See 1 more Smart Citation